KARAKTERISTIK KIMIA DAN UJI ORGANOLEPTIK BOLU GULUNG DARI TEPUNG BIJI NANGKA - Agnes Akaso; Musrowati Lasindrang; Zainudin Antuli (Jambura Journal of Food Technology, 2021)
The research aimed at finding out the Chemical Characteristics and Organoleptic Test of Roll Cake made of Jackfruit Seed Flour. The design used in this research was a single factor Randomized Block Design (RBD) with 4 treatments and 3 replications. The finding obtained that the treatment combination between jackfruit seed flour and wheat flour had a significant influence towards the proximate and organoleptic values of role cake. Moreover, the characteristic of role cake made of jackfruit seeds flour and wheat flour that could be accepted by panelist was the formulation of jackfruit seed flour of 25% : wheat flour of 75% : color of 5.67 (slightly like), flavor of 5.70 (slightly like), taste of 6.03 (like), texture of 5.73 (slightly like). The result of proximate analysis involves the water content for 16.01%, ash content for 2.24%, fat content for 5.67%, protein content for 10.62%, and carbohydrate content for 49.19%.